Histiocytoid Sweet Syndrome: A Rare Variant of Classic Paraneoplastic Dermatosis in Relation to Myelodysplastic Syndrome - A Case Report - Dev, Tanvi; Agarwal, Shipra; Khandpur, Sujay (Indian Journal of Medical and Paediatric Oncology, 2020)
Histiocytoid Sweet syndrome is a distinctive variant of Sweet syndrome, which is more frequently associated with myelodysplastic syndromes (MDS) than the latter. We describe a 59-year-old woman, diagnosed with MDS 4 months back, who developed sudden onset of rapidly progressing multiple painful erythematous papules and plaques on bilateral forearms, without any systemic complaints. The biopsy revealed interstitial and perivascular infiltrate of immature histiocytoid cells (positive for CD 68, myeloperoxidase, lysozyme, and CD15), along with papillary dermal edema. The eruption resolved with topical steroids in 3 weeks.
Keywords: Histiocytoid Sweet syndrome; myelodysplastic syndrome; paraneoplastic dermatoses